2011
DOI: 10.1214/11-sts360
|View full text |Cite
|
Sign up to set email alerts
|

On Instrumental Variables Estimation of Causal Odds Ratios

Abstract: Inference for causal effects can benefit from the availability of an instrumental variable (IV) which, by definition, is associated with the given exposure, but not with the outcome of interest other than through a causal exposure effect. Estimation methods for instrumental variables are now well established for continuous outcomes, but much less so for dichotomous outcomes. In this article we review IV estimation of so-called conditional causal odds ratios which express the effect of an arbitrary exposure on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(145 citation statements)
references
References 58 publications
2
141
0
1
Order By: Relevance
“…We found that the two-stage method using the whole sample in the first-stage regression gave estimates close to the PLOR. The adjusted two-stage method gave biased results in this case, even with no covariate effect, similar to the bias of the adjusted two-stage method observed by Vansteelandt et al under the null [3].…”
Section: Further Simulationssupporting
confidence: 82%
See 3 more Smart Citations
“…We found that the two-stage method using the whole sample in the first-stage regression gave estimates close to the PLOR. The adjusted two-stage method gave biased results in this case, even with no covariate effect, similar to the bias of the adjusted two-stage method observed by Vansteelandt et al under the null [3].…”
Section: Further Simulationssupporting
confidence: 82%
“…For a binary outcome Y = 0, 1, the conditional odds ratio (COR) is defined as the odds ratio for unit increase in the risk factor from x to x + 1 for a given value of v: (1) where and Y|(σ X = x, V = v) is the outcome random variable, conditional on covariate level v, where the risk factor level is set to x using the σ X notation for intervention Pearl [21]. Under the assumptions that Y equals Y|(σ X = x, V = v) if X = x and V = v (consistency) and that Y(x) ⫫ X|V (ignorability) [22], this can be expressed as: (2) In general, the COR may be a function of x and v, although in a logistic-linear model of association, where the logit of the probability of outcome (π) is a linear function in X and V with no interaction term: (3) the COR is exp(β 1 ) independently of x and v. This is the odds ratio estimated by a logistic regression of Y on X and V.…”
Section: Conditional and Population Odds Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the modelling assumptions are very often knowingly violated in applied MR studies when the outcome is binary and the SNP-outcome association is measured an odds ratio [5]. Indeed, the MR study we analyse in this paper relates to a binary outcome.…”
Section: Heterogeneity Assessmentmentioning
confidence: 99%